Planning Innovation and Regional Development: the Spreading of Urban Strategic Planning in Southern Italy - Ignazio Vinci (European Regional Science Association (ERSA), 2011)
For decades the Italian system of planning has been strongly characterized by a regulatory approach and the question of cities' development had been taken into account within general land use plans. In the 1990s this approach has been considered a strong constraint on the regeneration of cities and the revitalization of their economic potential. Therefore, in the last decade the improvement of flexibility and participation within planning processes were considered primary objectives both at regional and local levels. In addition to spatial regulatory plans, large and medium sized cities became increasingly interested in developing urban strategic plans following the model of some European "success stories" of urban regeneration (such as Barcelona, Lyon, Glasgow). In a first phase, these planning experiments were prevalently carried out by the cities of the Northern regions (such us Torino, Firenze, Venezia, Trento) and supported by strong voluntary public-private partnerships. In a second phase, after a financial programme by the Ministry of Economy, more then 150 cities in the Southern regions started strategic planning processes. These latest strategic plans (at present under observation both from policy makers and urban-regional scientists) should be evaluated in a very different way in comparison with the strategic plans carried out in Northern Italy. That's for two main reasons: First, because the majority of Southern cities still lag behind from an economic point of view, in addiction to very problematic governance environments and fragmented local societies; Secondly, as a consequence of the financial support provided to municipalities, because the national and the regional authorities require Southern cities to improve, through strategic planning, their capacity to implement effective regeneration programmes and to increase their access to the EU structural funds. Starting from these distinctive issues, this paper aims to critically discuss the spreading of strategic planning in Southern Italian regions, trying to analyse the ongoing process of innovation as regards the objectives undertaken at national level.
Keywords: 330